The "eternal character" of austerity measures in European crisis policies: Evidences from the Fiscal Compact discourse in Austria - Stephan Pühringer (Cusanus Hochschule, Institut für Ökonomie und Institut für Philosophie, 2017)
The European Fiscal Compact (FC) entered into force by 1 January, 2013 in 25 EU Member States. With the ratification the signatory countries commit significant parts of their budget to the European Commission and the European Court of Justice, which indicates a shift of power from legislative to executive authorities and the judiciary. In the aftermath of the economic crisis there can be observed a strong tendency to interpret the financial and economic crisis mainly as a sovereign debt crisis without any connection to the preceding crisis. This is reflected in several recommendations, which limit the scope of political decision-making in order to "calm financial markets". Applying an analysis of the public discourse about FC in three leading Austrian newspapers from December 2011 (the initial debate at an EU Summit) to July 2012 (the ratification in the Austrian parliament), the dominant rationale as well as legitimization and argumentation patterns will be examined. The methodology adopted in the article is based on a combination of critical discourse analysis and conceptual metaphor theory in order to illustrate the effectiveness of marketradical thinking of specific economic elites in public discourse. It can be shown that the public discourse about economic policies yet in a time of a potential "crisis of economics" is still dominated by economic ideas or "economic imaginaries" (implicitly) preferring austerity measures to active fiscal policies.
Keywords: B19; E50; E61; E65; G18; G38; Z18; 330; austerity; critical discourse analysis; metaphor analysis; economic imaginaries; Fiscal Compact; Austria